1. CHARACTERISTICS OF BRONCHIECTASIS ON HRCT OF COPD PATIENT AT BINH DINH TUBERCULOSIS AND LUNG DISEASE HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2025)
COPD and Bronchiectasis are characterized by fixed airway obstruction and chronic cough. Detection of bronchiectasis on high-resolution computed tomography in COPD patients may indicate the presence of more advanced ventilatory dysfunction, frequent exacerbations, and bacterial colonization.Objectives: 1. Determine the rate of bronchiectasis in COPD patients; 2. Describe features of bronchiectasis on HRCT and related factors.Material and methods: 84 COPD patients were hospitalized from March 2020 to April 2022 at the Tuberculosis and Lung disease Hospital of Binh Dinh province.Study methods descriptive.Results: The rate of bronchiectasis in COPD patients 48.8%. The most common morphology of bronchiectasis is cylindrical 41.4%, cystic 26.8%, varicose 15.9%, mixed 12.2%. Lower lobe position 46.3%, middle lobe 34.1 %, upper lobe 19.5%. Distribution of two lungs 51.2%, left lung 36.6%, right lung 12.2%.Conclusion: the incidence of bronchiectasis in COPD patients is higher, cylindrical images are common in the position of the lower and middle lobes in the distribution of the two lungs.
Keywords: Bronchiectasis; COPD